The Legal and Credit Status of the Project Products’ ‎Sale Contract in the Chain of Project-Oriented ‎Financing Contracts: the Role of Sale’s Contract ‎Terms in Project Bankability - Shadi Kasnavi; Mahmud Bagheri (پژوهش های حقوق تطبیقی, 2022)
Project-oriented financing as a method of attracting capital - unlike other methods of financing - does not rely on the credit and guarantee of the investor and requires the bankability of the project, and this bankability itself is affected by the performance of the project and the production of liquidity of the project. In this regard, the sale’s contract as a legal and credit instrument, with a prominent role in generating project liquidity, is considered a key component of the project's bankability, therefore, it is necessary for the lender to be sure of the sale of the product according to the expected conditions. But the implementation of the sale’s contract is also associated with risks, and bankability is realized only on the condition of optimal management of these risks and establishing special contractual conditions for allocating them to actors who have a higher ability to manage risk. In this manner, the design method of the sales contract plays a direct role in attracting capital from the financier for the implementation of industrial projects.